2019
DOI: 10.1055/s-0039-1688551
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Maximal Isometric Quadriceps Strength after the Application of Ultrasound-Guided Percutaneous Neuromodulation of the Femoral Nerve: A Case Series

Abstract: Introduction For those individuals who have suffered an injury to the knee or undergone a surgical intervention, the early recovery of the muscle strength contraction properties of the quadriceps is essential for a favorable recovery and for a return to the activities of daily living and other work- or sports-related activities. Objectives To evaluate the changes in maximal isometric strength (MIS) of the quadriceps muscle after the application of ultrasound-guided percutaneous neuromodulation (US-gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 26 publications
0
32
0
1
Order By: Relevance
“…También, Ilfeld y col., 23 encontraron una disminución del dolor tras un tratamiento de NMP-e sobre el nervio femoral en pacientes con reconstrucción de ligamento cruzado anterior. Por otro lado, Álvarez-Prats y col., 27 demostraron un aumento inmediato de la fuerza isométrica del cuádriceps tras la estimulación del nervio femoral en pacientes con dolor de rodilla. Los resultados de este estudio añaden que, respecto a los efectos obtenidos, el porcentaje de cambio es mayor a las 24 horas de una única intervención.…”
Section: Discussionunclassified
“…También, Ilfeld y col., 23 encontraron una disminución del dolor tras un tratamiento de NMP-e sobre el nervio femoral en pacientes con reconstrucción de ligamento cruzado anterior. Por otro lado, Álvarez-Prats y col., 27 demostraron un aumento inmediato de la fuerza isométrica del cuádriceps tras la estimulación del nervio femoral en pacientes con dolor de rodilla. Los resultados de este estudio añaden que, respecto a los efectos obtenidos, el porcentaje de cambio es mayor a las 24 horas de una única intervención.…”
Section: Discussionunclassified
“…However, most of the studies assessing the effects of PENS have been conducted in chronic pain populations. A recent study found that PENS could be a potentially effective technique for increasing isometric strength of the quadriceps in inhibited musculature in subjects with unilateral knee pathology [ 16 ]. Since therapeutic interventions focusing on the voluntary quadriceps muscle activation could improve the efficacy of exercise for strength improvement [ 32 ], PENS could be a useful procedure to improve physical performance to be used combined with exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure evoked pain-free maximal muscle contractions in 10 sequences of 10 s, each one with 10 s rest period between series according to Álvarez-Prats et al [ 16 ] protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there is limited literature on US-guided PNM. It has been applied to treat lateral elbow pain [ 14 ], short hamstring syndrome [ 23 ], anterior knee pain [ 24 , 25 ], or lower back pain [ 26 ]; to improve the activity of the hallucis flexor longus [ 27 , 28 ] or quadriceps strength [ 29 ]; and to improve sport performance [ 30 ]. Regarding LE, Arias-Buría et al [ 14 ] described a case-report and they only treated a patient with LE by applying PNM to analyze its effect on pain.…”
Section: Introductionmentioning
confidence: 99%